Peningkatan Hasil Belajar Siswa Kelas X IPS 2 SMA 1 Wabula dengan Menggunakan Model Problem Based Learning pada Materi Litosfer dan Dampaknya Terhadap Kehidupan - Haryati Haryati; Sitti Kasmiati; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2025)
The learning outcomes of class X IPS 2 students at Senior High School 1 Wabula on the Lithosphere material remain low due to one-way teaching that provides little room for student engagement. This condition reflects the low quality of the geography learning process that needs to be improved. This study aims to describe student learning activities, describe teacher teaching activities, and determine the improvement of student learning outcomes in class X IPS 2 Senior High School 1 Wabula taught using the Problem Based Learning model on the Lithosphere and Its Impact on Life material. The results of the study show an increase in student learning activities from the "fair" category to "good," an improvement in scores related to teacher teaching activities from the "fair" category to "good," and the achievement of the success indicator related to student learning outcomes, where the minimum mastery criterion of ≥ 75% was achieved, with 83% of students obtaining a score of ≥ 75. Thus, it can be concluded that the application of the Problem Based Learning model on the Lithosphere and Its Impact on Life material is effective in improving student learning activities, the quality of teacher teaching activities, and student learning outcomes in class X IPS 2 Senior High School 1 Wabula.